A familial chromosome 4p16.3 terminal microdeletion that does not cause Wolf-Hirschhorn (4p-) syndrome - Osundiji, Mayowa Azeez; Kahn, Eva; Lanpher, Brendan (Chromosome research, 2024)
Chromosome 4p16.3 microdeletions are known to cause Wolf–Hirschhorn syndrome (WHS), which is characterized by a distinct craniofacial gestalt and multiple congenital malformations. The 4p16.3 region encompasses WHS critical region 1 (WHSCR1) and 2 (WHSCR2). The WHSCR contains several genes that have been implicated in the WHS phenotype including: WHS candidate 1 [ WHSC1 (aka NSD2 , OMIM 602952)], WHS candidate 2 [ WHSC2 (aka NELFA , OMIM 606026)], and LETM1 (OMIM 604407). Although several patients harboring 4p16.3 microdeletions that are associated with WHS phenotypes have been reported, the precise molecular underpinnings of WHS are subjects of active investigations. The potential role(s) of genes within the 4p16.3 are increasingly being investigated. Here we report a novel 4p16.3 terminal microdeletion that is not associated with the characteristic WHS phenotype. We studied Individual A (7-months-old female) and her father, Individual B (27-year-old), who both carry a terminal 4p16.3 microdeletion (about 555 kb) that is distal to the WHSCR1 and WHSCR2, and does not include WHSC1 , WHSC2 , or LETM1 . Overall, our findings expand the phenotypic spectrum associated with 4p16.3 microdeletions and support the previous observations that, in some individuals, microdeletions within 4p16.3 region may not be sufficient to cause WHS.